Impact of Environmental, Social and Governance Index on Financial Performance of Companies in India (Journal of Informatics Education and Research, 2024)
The effect of Environmental, Social, and Governance (ESG) indicators on the financial performance of businesses in [insert particular industry or location] is investigated in this study. Investors, stakeholders, and corporate decision-makers must comprehend the connection between ESG elements and financial outcomes as sustainable policies and responsible corporate governance gain traction. Historically, the primary factor used to determine wise investment choices has been a company's worldwide financial performance. However, in addition to financial indications, other non-financial elements have also been more prevalent in fund managers' and investors' thinking over the past 20 years. There is little doubt that the hint points to the governance, social, and environmental (ESG) elements. Focus is being placed on long-term sustainable wealth maximization targets that incorporate ESG factors. It is well known that environmental, social, and governance (ESG) concerns pose a risk to company and can distort financial results. Numerous studies have been carried out to investigate the relationship between a company's financial performance (FP) and its ESG policies. However, the majority of research investigations have been conducted abroad, and reports of the relationships between these two elements have produced a variety of contradictory results. The purpose of this article is to investigate how ESG policies affect FP of organizations on both an individual and group level. ESG practices have been proxied by the ESG score provided by CRISIL (Credit Rating and Information Services India Limited). The financial performance of 200 carefully chosen Indian enterprises across various sectors has been represented by the use of Tobin Q, a market-based indicator, return on capital employed, and return on assets, accounting indicators.